Asia, Australia and New Zealand Dyspnoea in Emergency Departments (AANZDEM) study: Rationale, design and analysis. (4th May 2015) - Kelly, Anne‐Maree; Keijzers, Gerben; Klim, Sharon; Graham, Colin A; Craig, Simon; Kuan, Win Sen; Jones, Peter; Holdgate, Anna; Lawoko, Charles; Laribi, Said; AANZDEM Study Group
Abstract Objectives Shortness of breath is a common reason for ED attendance. This international study aims to describe the epidemiology of dyspnoea presenting to EDs in the South East Asia‐Pacific region, to compare disease patterns across regions, to understand how conditions are investigated and treated, and to assess quality of care. Methods/Design This is a prospective, interrupted time series cohort study conducted in EDs in Australia, New Zealand, Singapore, Hong Kong and Malaysia of consecutive adult patients presenting to the ED with dyspnoea as a main symptom. Data were collected over three 72 h periods in May, August and October 2014 (autumn, winter and spring), and included demographics, comorbidities, mode of arrival, usual medications, pre‐hospital treatment, initial assessment, ED investigations, treatment in the ED, ED diagnosis, disposition from ED, in‐hospital outcome and final hospital diagnosis. The primary outcomes of interest are the epidemiology and outcome of patients presenting to ED with dyspnoea. Secondary outcomes of interest are seasonal and geographic comparisons of diagnoses and outcomes, disease‐specific descriptions of epidemiology, investigation, treatment and disposition, and compliance with treatment guidelines. Discussion This novel study will explore dyspnoea from the viewpoint of the patient's symptom (shortness of breath) rather than that of a single disease. The results will provide robust data about the epidemiology, investigation, treatment and disposition of this diverse patient group. The obtained data also have the potential to inform service planning and to quantify the proportion of patients with mixed cardiac and respiratory disease.